Performance Indicator of Diskominfo XYZ City Based on IT Balanced Scorecard - Iqbal Santosa; Rahmat Mulyana; Nabila Nur Najmi Laila (IJAIT (International Journal of Applied Information Technology), 2022)
In managing the government, XYZ City is assisted by the Department of Communication and Information (Diskominfo) whose function is to formulate technical policies in the fields of communication, informatics, and public relations. XYZ city performance results are reported annually in the Government Agency Performance Accountability Report (LAKIP). In the 2020 LAKIP, it was still found that the formulation of performance indicators was not relevant to the goals/targets to be achieved, and it was also found that performance indicators were not clear how to be measured. In addition, there is a discrepancy between the formulation of the document performance indicators and the performance indicators in the e-SAKIP application. Because it is related to the application, this is the domain of the Diskominfo XYZ City. This study aims to produce a design of performance indicators both at the Diskominfo XYZ City and each field in the Diskominfo XYZ City using the IT Balanced Scorecard approach that has been adopted by COBIT with the term COBIT Goals Cascade. This research produces Enterprise goals, IT-Related Goals, and KPIs for each strategic target in each IT field at the Diskominfo XYZ City.